The RELIGIOUS MODERATION LEARNING STRATEGIES in the DIGITAL ERA: Study in the Indonesian Leimena Institute Program - Sumiati, Sumiati; Makmur, Makmur; Zulfah, Zulfah; Haris, Mardiana; Jamalia, M. N (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Religious moderation is essential in promoting peaceful coexistence in diverse societies, particularly in multicultural contexts like Indonesia. In the digital era, technological advancements offer new opportunities to enhance the understanding of religious moderation through innovative learning strategies. Purpose: This study examines the learning strategies for religious moderation in the digital era, focusing on the Cross-Cultural Religious Literacy (LKLB) program initiated by the Leimena Institute. The research investigates how digital learning strategies can effectively promote religious moderation in multicultural societies, particularly in Indonesia, where diversity in religion, culture, and ethnicity is prominent. Method: The study employs a qualitative research design, combining library research and field research to gather comprehensive insights into the program’s methodology and impact. Data were collected through interviews, observations, and the analysis of multimedia documents, including recordings of webinars and seminars. Result: The findings indicate that the blended learning approach, which integrates both online and offline methods, has proven to be highly effective in enhancing participants' understanding of religious moderation. Over 9,175 alumni have participated in the program, benefiting from discussions led by speakers from diverse religious and cultural backgrounds. Conclusion: The study concludes that the Leimena Institute, through its innovative learning strategies, plays a crucial role in fostering social harmony and preventing extremism in the digital era. The research contributes to the literature on technology-based religious education, offering valuable insights for future developments in religious moderation learning strategies.